Research on Spectroscopy Modulation of a Distributed Feedback Laser Diode Based on the TDLAS Technique - Li, Bin; Xue, Liang; Ji, Nan; Wei, Da Hui (International Journal of Optics, 2021)
Laser current and temperature control circuits have been developed for a distributed feedback laser diode, which is applied as the light source of a tuneable diode laser absorption spectroscopy system. The laser’s temperature fluctuation can be limited within the range of −0.02 to 0.02°C, and good operation stability was observed through 15 hours of monitoring on the emitting wavelength of the laser. Response time of temperature modulation was tested which is suitable for the tuning requirements of gas detection systems. Laser current can be injected within the range from 40 to 80 mA. In addition, a linear power supply circuit has been developed to provide stable and low-noise power supply for the system. The physical principles of laser modulation theory are discussed before experiments. Experiments show that the output wavelength of the laser can be tuned accurately through changing the working current and temperature. The wavelength can be linearly controlled by temperature at 0.115 nm/°C (I = 70 mA) and be controlled by current at 0.0140 nm/mA (T = 25°C). This is essential for the tuneable diode laser absorption spectroscopy systems. The proposed cost-effective circuits can replace commercial instruments to drive the laser to meet the requirements of methane detection experiments. It can also be applied to detect other gases by changing the light source lasers and parameters of the circuits.